2020
DOI: 10.1007/s42452-020-03535-y
|View full text |Cite
|
Sign up to set email alerts
|

A case study on mineralogy and physico-mechanical properties of commercial bricks produced in Nepal

Abstract: Uses of clay brick have practiced since ancient times in the Kathmandu valley of Nepal as structural materials for the construction of historical monuments, temples, and even modern buildings so on. However, their durability and sustainability properties are less studied scientifically in Nepal. Taking into consideration, analysis of mineralogical phases and physico-mechanical properties of modern clay bricks of Nepal was carried out using X-ray powder diffraction as well as Fourier transform infra-red techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…However, the Vp of the saturated samples showed values between 1666 and 2232 m/s. Based on previous studies, the bricks have a wide variation in their constituent mineral types and contents, physical characteristics (especially porosity), and pore size distribution [ 53 ], which strongly affect the Vp. As a result, Vp values of the bricks vary in a wide range.…”
Section: Resultsmentioning
confidence: 99%
“…However, the Vp of the saturated samples showed values between 1666 and 2232 m/s. Based on previous studies, the bricks have a wide variation in their constituent mineral types and contents, physical characteristics (especially porosity), and pore size distribution [ 53 ], which strongly affect the Vp. As a result, Vp values of the bricks vary in a wide range.…”
Section: Resultsmentioning
confidence: 99%
“…The compressive strength of 33 brick samples from the Bhaktapur District ranges from 7.83 MPa to 22.10 MPa (Shrestha, 2019). The compressive strength of 49 brick samples of 17 grades was reported to range from 3.35 to 10.53 MPa (Chapagain, 2020). On seven Kathmandu brick samples, the compressive strength ranged from 5 to 23 MPa (Bhattarai et al, 2018).…”
Section: Field and Laboratory Testing Resultsmentioning
confidence: 99%
“…According to Shrestha (2019), the apparent porosity value is between 19.28 and 53.99%. According to Chapagain (2020), the test findings show an apparent porosity at between 10% and 40%. Similar to this, Bhattarai et al (2018) demonstrated that the test result fell between 17 to 33%.…”
Section: Field and Laboratory Testing Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another physical property for the compressive strength difference is density. Solid brick density is almost twice the density of hollow brick, and there is a direct relationship between the density and compressive strength of the units [ 44 ]. The type of production and burning temperature are two factors affecting the compressive strength in production technology.…”
Section: Resultsmentioning
confidence: 99%